Loss of natural heritage from the geomorphological perspective – Do geomorphic processes shape or destroy the natural heritage? - Komac, Blaž; Zorn, Matija; Erhartič, Bojan (Acta geographica Slovenica, 2011)
This study deals with geomorphological natural features (geomorphosites) relative to the natural processes that create, shape, or destroy such features. As a rule, geomorphologic processes are geographical constants in the landscape although some, due to their high magnitude or low frequency of occurrence, can be seen as an exception (e.g., natural disasters). The importance of geomorphosites is relative to their size, rarity (spatial distribution), and duration (existence in time), which depend on both the frequency and magnitude of geomorphological processes and on the standards of the observer. Human influence and perception of geomorphosites is also important in this regard.